The Role of Health Workers in Combating TB-HIV (Case Study at Panti Wilasa Hospital Dr. Cipto Semarang) - Nur Azizah; Resti Nurhayati; Hartanto Hartanto (Soepra Jurnal Hukum Kesehatan, 2022)
Abstract: The incidence of TB-HIV is high and life-threatening, while on the other hand, TB-HIV patients have the right to get financial assistance in health services. Therefore, integrated health services are needed within the framework of the National Health Insurance. Health workers are an important aspect in the various health care approaches to patients with TB-HIV. This study aims to determine and examine the role of Health Workers in TB-HIV control and obstacles that are faced by Health Workers in carrying out their roles at Panti Wilasa Dr. Cipto Semarang Hospital.This research is a qualitative research with a sociological juridical approach. The data collection method used is literature study and field study. Primary data were obtained from interviews with the Semarang City Health Office, health workers and patients at Panti Wilasa Dr. Cipto Semarang Hospital. Secondary data consists of laws and regulations, books and journals.From the results of the research and discussion, it was concluded that the role of the Semarang City Health Office and Health Workers, such as General Practitioners, Specialist Doctors, Nurses, Laboratory and Pharmacy Officers at Panti Wilasa DR. Cipto Semarang hospital in the prevention of TB-HIV has been implemented well, but not optimal. This is influenced by: juridical aspects, sociological aspects, and dynamic aspects. The Problems faced by Health Workers in carrying out their role in TB-HIV control are often finding dishonest patients, patients who do not take medication, negative views of patients towards health workers, psychologically declining patients who tend to close themselves off from their families, Hospital services that are not integrated, lack of supporting hospital facilities, lack of health workers to  track patients' house, patients who have never seen a doctor, patients unable to take the TB-HIV medicine due to their work schedule, and no specific provisions were found that regulate the role of health workers in hospitals that can be used as the basis for legal protection in the implementation of TB-HIV disease control.Keywords: Tuberculosis, HIV, Health Workers, Role, Countermeasure Management